Identifikasi Kebutuhan Energi Operasional Sekolah Alam Tasdiiqul Insan Di Desa Curugrendeng, Subang, Jawa Barat - Doane Puri Mustika; Nur Hasyyati Luqiyana; Erwin Yusuf (CV. Multi Kreasi Media, 2025)
Tasdiiqul Insan Nature School in Curugrendeng Village, Subang Regency, West Java Province faces challenges in meeting the demand for electrical energy for educational purposes, as it is not yet connected to the PLN network and relies on unstable supplies from residents' homes. This Community Service Program aims to identify the school's operational energy needs and the potential for implementing renewable energy-based solutions. Activities are carried out through field surveys, energy consumption measurements, and analysis of solar energy potential based on local solar intensity data. The identification results show that the main energy needs include classroom lighting, fans, and learning support devices, with a total estimated energy consumption of ±2 kWh per day. This information serves as a crucial basis for designing a renewable energy supply system that is both appropriate and sustainable for the future.